2016
DOI: 10.1080/15476286.2016.1218589
|View full text |Cite
|
Sign up to set email alerts
|

Decoding sORF translation – from small proteins to gene regulation

Abstract: Translation is best known as the fundamental mechanism by which the ribosome converts a sequence of nucleotides into a string of amino acids. Extensive research over many years has elucidated the key principles of translation, and the majority of translated regions were thought to be known. The recent discovery of wide-spread translation outside of annotated protein-coding open reading frames (ORFs) came therefore as a surprise, raising the intriguing possibility that these newly discovered translated regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 135 publications
2
43
0
4
Order By: Relevance
“…However, as it has been found for sORFs or ncRNAs, intraRNAs encoded isoforms might present fine tuning regulatory roles that are yet to be discovered. It is also possible that the isoform itself does not play a role as protein but, similarly to what is known for uORF products [20,75], its translation process could regulate a downstream gene translation via ribosome interference if the intraRNA is part of a polycistronic transcriptional unit. In this scenario, it would be conceptually appropriate to rethink an intraORF as an uORF of the following gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as it has been found for sORFs or ncRNAs, intraRNAs encoded isoforms might present fine tuning regulatory roles that are yet to be discovered. It is also possible that the isoform itself does not play a role as protein but, similarly to what is known for uORF products [20,75], its translation process could regulate a downstream gene translation via ribosome interference if the intraRNA is part of a polycistronic transcriptional unit. In this scenario, it would be conceptually appropriate to rethink an intraORF as an uORF of the following gene.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent findings that prokaryotes in general have high fractions of translated leaderless mRNAs [18,19] and sORFs (small open reading frames) [20,21] make the realization of intraRNAs coding potential worth investigating. Pervasive translation of intraRNAs would include prokaryotes into the meaningfulness of protein isoforms debate [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several examples show that mutations creating or suppressing an uORF led to a decrease or increase in the downstream canonical protein expression (Cabrera-Quio et al 2016). One of the best studied examples of protein expression regulation by uORF translation is that of the GCN4 protein (Natarajan et al 2001).…”
Section: Smorfs: Mrna or Lncrna Orfs Smaller Than 100 Codonsmentioning
confidence: 99%
“…Upon starvation, translation re-initiation at the multiple uORFs is down-regulated and the GCN4 protein expression level thus rises (Hinnebusch 2005;Gunišová et al 2016). Multiple examples of uORF-mediated regulation of protein levels have been published; however, numerous studies also highlight the biological role of uORF-encoded peptides Cabrera-Quio et al 2016;Plaza et al 2017). In 2004, a proteomics study detected 54 novel microproteins mapped back to uORFs (Oyama et al 2004) and 40% of identified smORF-encoded peptides (SEPs) were from uORFs in Slavoff et al (2013).…”
Section: Smorfs: Mrna or Lncrna Orfs Smaller Than 100 Codonsmentioning
confidence: 99%
See 1 more Smart Citation